2016
DOI: 10.18632/oncotarget.8176
|View full text |Cite
|
Sign up to set email alerts
|

Association of HMGCR polymorphism with late-onset Alzheimer's disease in Han Chinese

Abstract: The 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) acts as a potential genetic modifier for Alzheimer's disease (AD). Previous reports identified that HMGCR rs3846662 polymorphism is associated with biosynthesis of cholesterol in AD pathology. In order to assess the involvement of the HMGCR polymorphism in the risk of late-onset AD (LOAD) in northern Han Chinese, we performed a case–control study of 2334 unrelated subjects (984 cases and 1350 age- and gender-matched controls) to evaluate the genotype and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Conversely, the rs3761740 variant of HMGCR was not associated with AD in a Swedish case-control study 68. Another HMGCR polymorphism (rs3846662) may increase the mRNA and protein levels of HMGCR by affecting alternative splicing, and thereby contribute to the onset and progression of AD 6972. Additionally, gene polymorphisms affect the cholesterol-lowering response to statin treatment 7375…”
Section: Regulatory Mechanism Of Hmgcrmentioning
confidence: 99%
“…Conversely, the rs3761740 variant of HMGCR was not associated with AD in a Swedish case-control study 68. Another HMGCR polymorphism (rs3846662) may increase the mRNA and protein levels of HMGCR by affecting alternative splicing, and thereby contribute to the onset and progression of AD 6972. Additionally, gene polymorphisms affect the cholesterol-lowering response to statin treatment 7375…”
Section: Regulatory Mechanism Of Hmgcrmentioning
confidence: 99%
“…A study conducted in 11,884 twins has shown that genetic predisposition accounts for 58-79% of Alzheimer's disease cases (Gatz et al, 2006). Previous studies have indicated that genetic polymorphisms in protein tyrosine kinase 2b, presenilin 2, apolipoprotein E, cytochrome 46A1, disrupted-in-schizophrenia-1, 3-hydroxy-3-methylglutaryl-CoA reductase, and sortilin receptor 1 all play essential roles in the development of this disease (Chang et al, 2016;Huang et al, 2016;Jia et al, 2016;Li et al, 2016;Suzuki et al, 2016;Zhang et al, 2016;Zheng et al, 2016). Previous studies have reported that alcohol consumption is associated with risk of Alzheimer's disease (Piazza-Gardner et al, 2013;Berntsen et al, 2015;Ilomaki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a multifactorial neurodegenerative disease including many genetic and environmental factors (Chang et al, 2016, Li et al, 2008. The brain of the patients with AD is essentially characterized by neuronal and synaptic loss, extracellular plaques composed of amyloid-β peptides, and intraneuronal neurofi bril lary tangles consisting of hyperphosphorylated tau proteins (Saraswati et al, 2018, Yang et al, 2015.…”
Section: Introductionmentioning
confidence: 99%